The role of the dorsolateral and ventromedial prefrontal cortex in emotion regulation in females with major depressive disorder (MDD): A tDCS study. (April 2022) - Nejati, Vahid; Majidinezhad, Maryam; Nitsche, Michael
Abstract: Background: Individuals with major depressive disorder (MDD) have deficits in emotion regulation, which plays a putative role in psychopathology. The ventromedial prefrontal cortex (vmPFC) and dorsolateral prefrontal cortex (dlPFC) are assumed to be involved in respective processes. In the present study, we aimed to explore the effect of stimulation over the dlPFC and vmPFC on emotion regulation in female with MDD. Material and methods: Twenty women with MDD performed the Emotional Stroop, Emotional Go/No-Go, and Emotional 1-Back tasks during transcranial direct current stimulation (tDCS) in three separate sessions with the following electrode montages: anodal dlPFC (F3)/cathodal vmPFC (Fp2), anodal vmPFC (Fp2)/cathodal dlPFC (F3), and sham stimulation. Results: Independent of the valence of the respective stimuli, accuracy and speed of interference control, accuracy of pre-potent inhibition, and accuracy, but not speed, of working memory performance improved during anodal left dlPFC/cathodal right vmPFC stimulation. Independent of stimulation conditions, interference control was reduced for sad faces, as compared to happy and neutral faces, and working memory performance was faster for happy than for neutral and sad faces. For the impact of stimulation on specific emotional qualities, anodal left dlPFC/cathodal right vmPFC, compared to sham stimulation, led to improved interference control of sad and neutral faces in the emotional Stroop task, as shown by faster reaction times. Furthermore, in that task accuracy with respect to neutral and happy face conditions was higher during both real stimulation conditions, as compared to sham stimulation. Conclusion: The dlPFC is involved in emotion regulation in MDD. Emotional valence is moreover relevant for the effect of stimulation over this area on interference control in MDD.